Left atrial venous arterial extracorporeal membrane oxygenation for biventricular failure in cardiogenic shock. (14th October 2021) - Eng, M; Al-Darzi, W; Basir, M; Singh-Kucukarslan, G; Villablanca, P; Koenig, G; Alaswad, K; Cowger, J; Oneill, W
Abstract: Background: Cardiogenic shock complicated by biventricular (BIV) heart failure is associated with high mortality. Venous-arterial extra-corporeal membrane oxygenation is limited by the increase of left ventricular (LV) afterload. Complex configurations of paired circulatory support devices have been used with mixed results due to vascular access complications. One way to simply vascular access is to place a transseptal cannula under echocardiographic guidance with a long fenestrated segment enabling simultaneous left and right sided unloading known as left-atrial venous arterial (LAVA) ECMO. Purpose: We aimed to review the safety and outcomes of LAVA ECMO utilized for shock at our institution. Methods: Retrospective analysis of our Hospital Cath Lab Database yielded 6 patients undergoing LAVA-ECMO for shock from 7/2020–3/2021. Patient characteristics, procedural data and outcomes were analyzed. Variables are either expressed as proportions or medians (Interquartile range; IQR). Results: Median age was 55.5 years (IQR, 51–61) and most patients were men (83.3%). Median baseline LV ejection fraction was 38% (IQR, 23–56%) and all had right ventricular dysfunction. 4/6 (66.7%) had severe valvular dysfunction including aortic regurgitation (2/6), mitral regurgitation (2/6) and mitral stenosis (1/6). One patient had a LV thrombus and hemodynamics necessitated LV unloading. Intracardiac echocardiography was used to guide the transseptal puncture in 5/6 (83%). Transesophageal echocardiography was used in one case. Procedural outcomes and hemodynamic variables are outlined in Tables 1 and 2 consecutively. One case of limb ischemia resulted from an embolus in the contralateral limb. LAVA-ECMO bridged 83% of patients to valve replacement, durable ventricular support or heart transplant (Table 1). Conclusions: LAVA-ECMO provides BIV support with a single circuit and successfully bridged patients without direct complications. Given the safety, efficacy and simplified configuration of LAVA-ECMO, prospective studies are indicated. Funding Acknowledgement: Type of funding sources: None.